2017
DOI: 10.1097/mib.0000000000001131
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine with Allopurinol

Abstract: Article first published online 27 April 2017Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Curffari et al[36] also discovered that the levels of DNA-TG metabolites were correlated with the erythrocyte 6TGN level, but not the total leukocyte level. However, a recent study performed by Coulthard et al[37] showed contradictory results, indicating that the exact function of DNA-TG still requires further validation in IBD. On the other hand, we performed this retrospective research to determine the cut-off levels of 6TGN for predicting TIL, which need to be validated in further prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Curffari et al[36] also discovered that the levels of DNA-TG metabolites were correlated with the erythrocyte 6TGN level, but not the total leukocyte level. However, a recent study performed by Coulthard et al[37] showed contradictory results, indicating that the exact function of DNA-TG still requires further validation in IBD. On the other hand, we performed this retrospective research to determine the cut-off levels of 6TGN for predicting TIL, which need to be validated in further prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Allopurinol is a xanthine oxidase inhibitor and when added to TP increases its metabolism through 5-IMPDH into 6-TGN. LDTA can be useful in "hypermethylators" (79), in which TGN levels are usually <230-400 pmol/8 × 10 8 and/or 6-MMP levels are over 5,700-6,000 pmol/8 × 10 8 (80), so that they are at risk of hepatotoxicity and refractoriness to TP (81).…”
Section: Using Low Dose Thiopurine and Allopurinolmentioning
confidence: 99%